Pendampingan Penulisan Buku Ajar Kepada Guru Sekolah dan Madrasah Ibtidaiyah di Kecamatan Andong Boyolali - Ngatmin Abbas; Mukhlis Fathurrohman; Edy Muslimin (Universitas Nurul Jadid, 2025)
This mentoring program aims to improve the skills of Elementary School (SD) and Madrasah Ibtidaiyah (MI) teachers in Kacangan Village, Andong District, Boyolali, in developing textbooks based on local wisdom and in accordance with the Merdeka Curriculum. The approach used is Participatory Action Research (PAR) and Workshop-Based Training, where teachers play an active role in the process of developing teaching materials. This activity includes training, discussion, and intensive assistance to compile and adapt textbooks so that they are more contextualized with student characteristics. The results of this mentoring showed a positive response from the teachers. A total of 61.5% stated that they would “Yes, definitely” implement the results of the workshop, while the other 38.5% answered “Maybe”. This reflects optimism as well as caution in the implementation of the program. This assessment shows that the strategies implemented are considered realistic and workable in daily learning. In addition, this approach also increases teachers' awareness of the importance of integrating local values in education. The implications of this program include improving the quality of learning and strengthening cultural identity in the developed textbooks. To ensure the sustainability of this program, support is needed through collaboration between schools, communities and local governments so that the innovations that have been introduced can continue. Thus, education in Kacangan Village can progress without losing its local cultural roots.